The Trend of Inclusive Learning Models: Systematic Review Study - Iryani, Endang; Hufad, Hufad; Rusdiyani, Isti (PPSDP International Journal of Education, 2023)
This study aims to analyze the trend of inclusive learning models with study criteria; the learning model tested as an inclusive learning model at various levels of education. the systematic review method refers to Castlebery with five study stages namely compiling, disassembling, reassembling, interpreting, and concluding. data collection using the published or perish application to collect articles from 2013 to 2023, with the keywords teaching model inclusive, teaching model for inclusive school, and teaching model for SEND (student education need disabilities) from Google Scholar. 200 journals have been screened with predetermined study criteria. The results of this study have shown that the trend is testing existing learning models by looking at their effectiveness and relevance to inclusive classes (62%), the trend is investigating learning models adapted to inclusive classes (15%), the trend is comparing learning models by looking for relevance to the inclusive class (15%), and trends describing the right model for use in the inclusive class based on a literature review (8%). The findings of this study can be used as a reference for teachers in conducting inclusive classroom learning, and researchers can formulate a more comprehensive learning model based on the analysis of the learning models studied in this study.